2020
DOI: 10.1002/cbf.3485
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐665 is down‐regulated in gastric cancer and inhibits proliferation, invasion, and EMT by targeting PPP2R2A

Abstract: Recently, microRNA-665 (miR-665) has been reported to function as both tumour suppressor and oncogene in several cancer types, including gastric cancer, hepatocellular cancer, and lung cancer. However, the biological function of miR-665 and its precise mechanisms in gastric cancer (GC) have not been well clarified. The aim of this study was to study the roles of miR-665/PPP2R2A axis in GC. The levels of PPP2R2A and miR-665 were detected by quantitative PCR assay in GC tissues and cell lines. Moreover, the biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
(57 reference statements)
4
18
0
Order By: Relevance
“…Previous studies revealed that knockdown of PR55α hindered non-small cell lung cancer cellular growth by increasing JUN T239 phosphorylation 19 . In gastric cancer, PPP2R2A expression is remarkably increased and downregulation of PPP2R2A also inhibits the proliferation and EMT of gastric cancer cells 20 . However, more studies have provided supporting towards the tumor suppressing role of PR55α.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that knockdown of PR55α hindered non-small cell lung cancer cellular growth by increasing JUN T239 phosphorylation 19 . In gastric cancer, PPP2R2A expression is remarkably increased and downregulation of PPP2R2A also inhibits the proliferation and EMT of gastric cancer cells 20 . However, more studies have provided supporting towards the tumor suppressing role of PR55α.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MiR-222 can suppress PPP2R2A expression and promote the proliferation or invasion of papillary thyroid cancer 20 , diffuse large B-cell lymphoma 19 and HCC 17 . But, miR-665 was reported to promote PPP2R2A overexpression and inhibit the proliferation and epithelial-mesenchymal transition of gastric cancer cells 22 . Speci cally, PR55α was lowly expressed in lung cancer, thyroid gland cancer, breast cancer, diffuse large B-cell lymphoma and HCC, but highly expressed in pancreatic cancer and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PPP2R2A is a target gene of miR-222 and is considered to be a tumor suppressor. 24,45 Studies have indicated that PPP2R2A regulates cancer development via AKT pathways. Zhang et al reported that Pits2 promotes PPP2R2A-mediated AKT inhibition and represses pancreatic carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 PPP2R2A is considered a tumor suppressor and participates in the proliferation, invasion and EMT of cancer cells. [24][25][26] Additionally, PPP2R2A is reported to modulate aggressive behaviors of cancer cells by blocking the AKT signaling. 27 The AKT signaling is closely associated with EMT.…”
Section: Introductionmentioning
confidence: 99%